The Analysis of Lexical Features in Makeup and Skincare Video Advertisements - Windy Gusti Dwiyanti (Jurnal Linguistik Terapan, 2024)
Most of video advertisements used certain linguistic styles, including lexical features in order to attract and persuade audiences. This paper investigates the use of lexical features in successful makeup and skincare video advertisements. The data sources used in this research were L’Oreal Paris and Rare Beauty as the makeup video advertisements. Then, Nivea, and Curology as the skincare video advertisements. The research design used is case study which is a form of qualitative research. This study attempted to investigate what linguistic styles (lexical dan syntactical features) are used in the makeup and skincare video advertisements. Based on the result analysis, the researcher found that makeup and skincare video advertisements used 7 out of 10 types of lexical features, namely hyperbole, weasel word, familiar language, simple vocabulary, repetition, euphemism, and glamorization.